2019
DOI: 10.1002/term.2987
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix cues modulate Schwann cell morphology, proliferation, and protein expression

Abstract: Peripheral nerve injuries require a complex set of signals from cells, macrophages, and the extracellular matrix (ECM) to induce regeneration across injury sites and achieve functional recovery. Schwann cells (SCs), the major glial cell in the peripheral nervous system (PNS), are critical to nerve regeneration due to their inherent capacity for altering phenotype postinjury to facilitate wound healing. The ECM plays a vital role in wound healing as well as regulating cell phenotype during tissue repair. To exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…[45][46][47][48] For instance, it has been previously demonstrated that polydimethylsiloxane (PDMS) substrates can be fabricated over a broad range of physiologically relevant Young's Moduli to promote durotaxis and phenotype change of Schwann cells. [24,41] It was also shown that an intermediate substrate stiffness promotes the proliferation of Schwann cells and expression of the dedifferentiated Schwann cell marker c-jun. [24] In broader applications, the extracellular matrix has received a renewed interest in relation to rheological mediation of cell behavior during development, disease, and regeneration.…”
Section: Characterization Of Fiber Morphology Tensile Strength and mentioning
confidence: 99%
See 3 more Smart Citations
“…[45][46][47][48] For instance, it has been previously demonstrated that polydimethylsiloxane (PDMS) substrates can be fabricated over a broad range of physiologically relevant Young's Moduli to promote durotaxis and phenotype change of Schwann cells. [24,41] It was also shown that an intermediate substrate stiffness promotes the proliferation of Schwann cells and expression of the dedifferentiated Schwann cell marker c-jun. [24] In broader applications, the extracellular matrix has received a renewed interest in relation to rheological mediation of cell behavior during development, disease, and regeneration.…”
Section: Characterization Of Fiber Morphology Tensile Strength and mentioning
confidence: 99%
“…[24,41] It was also shown that an intermediate substrate stiffness promotes the proliferation of Schwann cells and expression of the dedifferentiated Schwann cell marker c-jun. [24] In broader applications, the extracellular matrix has received a renewed interest in relation to rheological mediation of cell behavior during development, disease, and regeneration. For instance, ECM stiffening has been directly linked to tumor progression for various cancers.…”
Section: Characterization Of Fiber Morphology Tensile Strength and mentioning
confidence: 99%
See 2 more Smart Citations
“…During regeneration, fibronectin is upregulated and increases Schwann cell spread and proliferation, and neurite outgrowth [35,36]. Besides from providing endogenous support, collagen, laminin, and fibronectin have been thoroughly investigated and shown to improve nerve regeneration in various rodent models as fillers for conduits [37][38][39][40], which has led to development of various biomimetic conduits [41].…”
Section: Discussionmentioning
confidence: 99%